THE ROLE OF MSMEs AND WOMEN ENTREPRENEURS IN DEVELOPMENT ECOMONIC IN INDONESIA: LITERATURE REVIEW, ANALYSIS AND DEVELOPMENT STRATEGY - Robert Sanjaya Sembiring; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
This study aims to understand the Role of MSMEs and Women Entreprenurs in development Economic. A country's economic development is strongly influenced by the quality of its human resources (HR) and the business sector that develops within them, and one of the strongest enablers is entrepreneurship through micro, small and medium enterprises (MSMEs), especially through women entrepreneurs. Entrepreneurship through MSMEs is gender neutral, anyone can be an entrepreneur and MSMEs play a strategic role in Indonesia's economic development and growth. However, the reality is that MSMEs face several challenges such as gender inequality, lack of awareness about entrepreneurship, lack of capital, limited access to finance and an unfriendly business climate. This study aims to analyse the role of MSMEs and women entrepreneurs in improving the economy, such as reducing unemployment, and the challenges and solutions in addressing these challenges.